Mathematical Literacy Seen from Learning Independency in Blended Learning with Project Based Learning Assisted by Moodle - Angreanisita, Wiwik; Mastur, Zaenuri; Rochmad, Rochmad (Universitas Negeri Semarang, 2021)
Mathematics literacy and learning independency have important roles for individuals’ decision making to solve life problems. One of such efforts within the growth of 4.0 industrial revolution era is by applying technology in learning. Blended learning model with PjBL assisted by Moodle is a learning alternative by using technology and two learning methods: offline learning by using PjBL and online learning by Moodle. This research aimed to describe mathematics literacy seen from learning independency on Blended learning with PjBL assisted by Moodle. This mixed method research used explanatory sequential design. The population in this study was 10th grade of MAN 2 Kota Pekalongan. The quantitative data was selected by purposeive sampling. The subject categorization was based on learning independency: high, moderate, and low. The findings showed that Blended leanring with PjBL assisted by Moodle was effective in improving mathematics literacy and student learning independency. The description of the improvement seen from learning independency obtained various results as shown by high learning independency which reached high and moderate mathematics literacy skills. Moderate learning independency students reached high, moderate, and low mathematics literacy skills. Meanwhile, the low learning independency students reached moderate and low mathematics literacy skills.